Virtual Work - Steinmann, Paul (Spatial and Material Forces in Nonlinear Continuum Mechanics, 2022)
This chapter capitalizes on the referential setting when introducing the notions of spatial and material virtual displacements and discussing the accompanying spatial and material virtual work principles.
CRIS-Team Scopus Importer:2022-04-15